Isatidis root polysaccharides ameliorates post-weaning diarrhea by promoting intestinal health and modulating the gut microbiota in piglets - Miao Zhou; Zenghao Yan; Deqin Wang; Chuyuan Li; Leli Wang; Rui Li; Jie Yin; Yulong Yin (Veterinary Quarterly)
This study aimed to investigate the effects of dietary isatidis root polysaccharide (IRP) on diarrhea, immunity, and intestinal health in weanling piglets. Forty healthy piglets were randomly assigned to five groups receiving varying dosages of IRP. The findings indicated that different concentrations of IRP significantly reduced diarrhea scores (p < 0.01). Notably, the serum levels of immunoglobulin A and immunoglobulin G increased linearly and quadratically (p < 0.01), while immunoglobulin M also showed a linear increase (p < 0.05) in IRP-fed piglets. The secretory immunoglobulin A levels in ileal contents were significantly higher compared to control piglets (p < 0.01). Key intestinal health parameters, including villus height, villus height-to-crypt depth ratio, and goblet cell numbers, showed linear and quadratic increases in both the jejunum and ileum (p < 0.05), while crypt depth decreased significantly (p < 0.01). Additionally, the expression of IL-10, ZO-1, occludin, and mucin2 was upregulated linearly and quadratically in IRP-fed piglets (p < 0.05). In cultured IPEC-J2 cells, ZO-1 and occludin expression levels significantly increased upon exposure to 400 μg/mL IRP (p < 0.01). Furthermore, the relative abundances of Escherichia coli, Ralstonia pickettii, and Desulfovibrio fairfieldensis decreased linearly with increasing dietary IRP concentration. In conclusion, IRP shows promise as an effective dietary supplement for mitigating diarrhea and enhancing intestinal health in early weaned piglets.